2013
DOI: 10.4236/jct.2013.47146
|View full text |Cite
|
Sign up to set email alerts
|

<i> Annonaa muricata </i> Linn Leaf Induce Apoptosis in Cancer Cause Virus

Abstract: Introduction: Now many studies conducted on the drug substance from nature that can serve as an anticancer agent as a potential chemoprevention agent, such as Annona muricata Linn leaf escort chemotherapy, which was flaring. The cancer cell in humans was included the loss of p53 protein function due to mutations in the protein gene. Other causes are that the p53 proteins are not functioning due to an increase in protein misfolding event chaperones and degradation events ubiquitous as binding by viral protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
25
0
2
Order By: Relevance
“…In the study conducted by Fidaningsih and Handayani, it is found that the best effect of the water extract of soursop leaves to inhibit proliferation is in the dosage of 75 mg/ml with an 88.45% inhibition rate [24]. On the other hand, in another study by Astirin et al, it is found that the dosage needed for alcohol-soluble soursop leaf extract to achieve the same effect is 2 mg/ml with 35.80% apoptotic figure [25]. Another study which assessed the effect of the leaves of Annona muricata against cancer cells described that the leaf extract could induce apoptosis in colon and lung cancer through the mitochondria and has the effect of activation of caspase-3 in leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Fidaningsih and Handayani, it is found that the best effect of the water extract of soursop leaves to inhibit proliferation is in the dosage of 75 mg/ml with an 88.45% inhibition rate [24]. On the other hand, in another study by Astirin et al, it is found that the dosage needed for alcohol-soluble soursop leaf extract to achieve the same effect is 2 mg/ml with 35.80% apoptotic figure [25]. Another study which assessed the effect of the leaves of Annona muricata against cancer cells described that the leaf extract could induce apoptosis in colon and lung cancer through the mitochondria and has the effect of activation of caspase-3 in leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A. muricata leaves were successively extracted using soxhlet apparatus [19][20][21][22]. A total of 55 g of A. muricata powdered leaves were first extracted with n-hexane until the solution turned colourless.…”
Section: Plant Extraction and Extract Preparationmentioning
confidence: 99%
“…If will be used then dissolved in a little phosphate of sodium 5 mM, pH 6.5 without NaCl. A solution of vortexed until late at, centrifuged, the sediment dumped and supernatant which is the fraction of protein included in conical tube [19,20]. Partition done with chloroform and the success of a partition monitored with the methods chromatography thin layer and a top part is taken fractionation of from the upper part of the results of the process of partition is by using liquid chromatography vacuum.…”
Section: J Curcas Leaf Extracts Preparationmentioning
confidence: 99%
“…Subsequently a precipitate during 24hr in culture medium than the Raji cell were grown in microplate with media plus extract with a nonlethal concentration of fractionation J. curcas leaf. of sampling was performed for 24 hrs [20].…”
Section: Treatment (Raji Cells Were Treated With Fractionated Extractmentioning
confidence: 99%
See 1 more Smart Citation